1984
DOI: 10.1177/001440298405100105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Full-Time Mainstreaming Program and a Resource Room Approach

Abstract: A study comparing the effects of a full-time mainstreaming approach for handicapped students with a resource room approach for similar students is reported. Results of the study suggest that the full-time mainstreaming approach, known as the Adaptive Learning Environments Model, exceeds the resource room approach in attaining desirable classroom processes, student attitudes, and student achievement in basic skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 7 publications
1
37
0
Order By: Relevance
“…Contrary to common assumptions, students with disabilities do not usually learn more in self-contained special education classrooms; equal or superior results are obtained when appropriate supports are provided in general education classrooms (Affleck, Madge, Adams, & Lowenbraun, 1988;Banerji & Dailey, 1995;Bunch & Valeo, 1997;Cole & Meyer, 1991;Freeman & Alkin, 2000;Fryxell & Kennedy, 1995;Hunt & Goetz, 1997;Ingraham & Daugherty, 1995;Logan & Keefe, 1997;Lipsky & Gartner, 1995;Madden, Slavin, Karweit, Dolan, & Wasik, 1993;McGregor & Vogelsberg, 1998;Schulte, Osborne, & McKinney, 1990;Waldron & McLeskey, 1998;Wang & Birch, 1984;Willrodt & Claybrook, 1995). Of course, educators are also concerned about the progress of students without disabilities; here the outcomes research is equally reassuring, with equal or superior academic, social, and behavioral outcomes for students without disabilities in inclusive general education classrooms compared to noninclusive classrooms (Holloway, Salisbury, Rainforth, & Palombar, 1995;Peck, Donaldson, & Pezzoli, 1990;Salend & Duhaney, 1999;Sasso & Rude, 1988;Sharpe, York, & Knight, 1994).…”
Section: Discussionmentioning
confidence: 92%
“…Contrary to common assumptions, students with disabilities do not usually learn more in self-contained special education classrooms; equal or superior results are obtained when appropriate supports are provided in general education classrooms (Affleck, Madge, Adams, & Lowenbraun, 1988;Banerji & Dailey, 1995;Bunch & Valeo, 1997;Cole & Meyer, 1991;Freeman & Alkin, 2000;Fryxell & Kennedy, 1995;Hunt & Goetz, 1997;Ingraham & Daugherty, 1995;Logan & Keefe, 1997;Lipsky & Gartner, 1995;Madden, Slavin, Karweit, Dolan, & Wasik, 1993;McGregor & Vogelsberg, 1998;Schulte, Osborne, & McKinney, 1990;Waldron & McLeskey, 1998;Wang & Birch, 1984;Willrodt & Claybrook, 1995). Of course, educators are also concerned about the progress of students without disabilities; here the outcomes research is equally reassuring, with equal or superior academic, social, and behavioral outcomes for students without disabilities in inclusive general education classrooms compared to noninclusive classrooms (Holloway, Salisbury, Rainforth, & Palombar, 1995;Peck, Donaldson, & Pezzoli, 1990;Salend & Duhaney, 1999;Sasso & Rude, 1988;Sharpe, York, & Knight, 1994).…”
Section: Discussionmentioning
confidence: 92%
“…Bear et al (2002) concluded that students with learning disabilities attending an inclusive classroom did not seem harmed even though they were comparing themselves to their peers in the regular classroom. Inclusion helps reduce stigma (Bauwens & Hourcade, 1991;Madden & Slavin, 1983) and develops positive self-perceptions as students participate as members of a classroom (Wang & Birch, 1984). Another finding asserted that the inclusive classroom would not likely develop positive self-perceptions unless students with disabilities were taught not to compare themselves to their peers (Bear, Clever & Proctor, 1991).…”
Section: Self-concept and Placementmentioning
confidence: 99%
“…A prime example was the Adaptive Learning Environments Model (ALEM) (Wang, Gennari, & Waxman, 1985). The empirical evidence viewing ALEM favourably (Wang & Birch, 1984a, 1984bWang, Peverly, & Randolph, 1984) was analysed critically, and found to be de cient and inconsistent with respect to design, analysis, and interpretation D. Fuchs & L.S.…”
Section: The Regular Education Initiativementioning
confidence: 99%